#
Verify whether the following are roots of the polynomial equation indicated against them:

2
Log in to add a comment

Log in to add a comment

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

Given ⇒ x² - 5x + 6 = 0

⇒x² -2x -3x + 6 = 0

⇒x(x - 2) - 3(x - 2) = 0

⇒ (x - 2)(x - 3)= 0

so

when & when

x - 2 = 0 ⇒x = 2 x - 3 = 0 ⇒x = 3

so verified the following are roots of the polynomial equation

⇒x² -2x -3x + 6 = 0

⇒x(x - 2) - 3(x - 2) = 0

⇒ (x - 2)(x - 3)= 0

so

when & when

x - 2 = 0 ⇒x = 2 x - 3 = 0 ⇒x = 3

so verified the following are roots of the polynomial equation

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

Substitute x=2

2² -5(2)+6

4-10+6

0

hence x-2 is a root

substitute x=3

3² -5(3)+6

9-15+6

0

hence x-3 is also a root.

2² -5(2)+6

4-10+6

0

hence x-2 is a root

substitute x=3

3² -5(3)+6

9-15+6

0

hence x-3 is also a root.